METHOD, APPROACH, AND TYPE OF HADIS SYARAH OF THE BOOK AL-MINHĀJ SHARAḤ ṢAḤĪḤ MUSLIM IBN AL-ḤAJJĀJ BY AL-NAWAWĪ (W.676 H.) - Takwallo; Abdurrohman (International Conference on Islamic Studies, 2025)
The purpose of writing this article is to review the role of Imam Muslim in the syarah of al-Minhaj by analyzing how the method, approach and style of the hadith commentary in it. The method used in this article is qualitative by using a historical approach, namely by tracing the biography of Imam Muslim’s personality and the ins and outs of his work entitled al-Minhaj Sharh Sahih Muslim. The result of this research is that this book was written because of istikharah conducted by Imam al-Nawawī after previously writing the sharah of Ṣaḥīḥ al-Bukhārī. The methods of syarah used by him are: muqārin, taḥlīlī, and ijmālī, his approach is linguistic, while his style is fiqhī. This book has been very influential for hadith scholars. Many of them have made this book their main source of reference, and many hadith scholars have even conducted research on this book.